2003
DOI: 10.1016/s0736-0266(03)00009-3
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term intermittent shear deformation improves the quality of cartilaginous tissue formed in vitro

Abstract: The formation of cartilaginous tissue in vitro is a promising alternative to repair damaged articular cartilage. However, recent attempts to tissue-engineer articular cartilage that has similar properties to the native tissue have proven to be difficult. The in vitroformed cartilaginous tissue typically has a similar proteoglycan content to native cartilage, but has a reduced collagen content and only a fraction of the mechanical properties. In this study, we investigated whether the intermittent application o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
133
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(140 citation statements)
references
References 39 publications
6
133
0
1
Order By: Relevance
“…Based on the premise that mechanical factors play an important role in the development and maintenance of healthy cartilage in vivo (Kiviranta et al, 1988;Beaupre et al, 2000;Grodzinsky et al, 2000), numerous investigators have shown that both dynamic compressive (Buschmann et al, 1995;Lee and Bader, 1997;Lee et al, 1998;Lee et al, 2000;Waldman et al, 2004) and shear (Waldman et al, 2003a) loading of chondrocytes in 3D culture stimulate the synthesis of cartilaginous ECM macromolecules. When the stimulus is applied intermittently over a long duration (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the premise that mechanical factors play an important role in the development and maintenance of healthy cartilage in vivo (Kiviranta et al, 1988;Beaupre et al, 2000;Grodzinsky et al, 2000), numerous investigators have shown that both dynamic compressive (Buschmann et al, 1995;Lee and Bader, 1997;Lee et al, 1998;Lee et al, 2000;Waldman et al, 2004) and shear (Waldman et al, 2003a) loading of chondrocytes in 3D culture stimulate the synthesis of cartilaginous ECM macromolecules. When the stimulus is applied intermittently over a long duration (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…When the stimulus is applied intermittently over a long duration (i.e. several weeks) the cells accumulate greater amounts of ECM which also results in the improved mechanical performance of the in vitro-formed tissue (Mauck et al, 2000;Mauck et al, 2003;Chowdhury et al, 2003;Waldman et al, 2003a;Waldman et al, 2003b;Waldman et al, 2004). Although the application of these relatively simple loading conditions has resulted in beneficial effects, articular cartilage in vivo is subjected to complex loading consisting of a combination of both compressive and shearing forces under normal physiological conditions (Mankin et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Among the techniques under development for cartilage regeneration, certain tissue engineering strategies combine primary chondrocytes with various scaffolds to grow tissue equivalents. The effects of specific physical parameters [19,24,28,39] and growth factors [5,12,40] have been widely studied using these systems in order to produce a tissue construct which, once implanted at the site of the cartilage lesion, should lead to a well-integrated and functional hyaline-like replacement tissue. Characterization of human [2,13], equine [21], bovine [1,7,11,35], rabbit [34] and mouse [25] cultured articular cartilage explants revealed that intrinsic metabolism of chondrocytes and their response to external factors vary with animal age.…”
Section: Introductionmentioning
confidence: 99%
“…It has been well documented that achieving native levels of collagen accumulation is more challenging than reaching native levels of proteoglycan accumulation in tissue-engineered cartilage. [44][45][46][47] Indeed, rapid GAG synthesis has been hypothesized to be an impediment to collagen synthesis in chondrocyte seeded agarose hydrogels, with recent studies demonstrating that inducing enzymatic GAG loss during the early phase of culture can increase the ultimate collagen concentration and tensile properties of the engineered tissue. 48 The local environment within SA constructs would appear to suppress sGAG synthesis while maintaining collagen synthesis at levels approaching that found in the agarose hydrogels.…”
mentioning
confidence: 99%